O kondycji polskiej edukacji domowej jako społecznego „subimago” (albo o niebezpieczeństwach metaforyzacji) - Budajczak, Marek (Kultura-Społeczeństwo-Edukacja, 2012)
The paper gives an ironic and short, both empirical and normative analysis of current Polish home education intertwined with a metaanalysis of the role of metaphors in the language of the educational sciences. Entomological metaphor of subimago helps here in revealing the social status quo of the mentioned „home education” in Poland. One can describe socioeducational reality using different forms of expression. Metaphorization is one of them, not always adequate, but indispensable as well as cognitively pleasant.